Hypertrophic cardiomyopathy with Jeune syndrome: The first reported case - Osman Güvenç; Saime Sündüs Uygun; Derya Çimen; Eyüp Aslan; Ali Annagür (KARE Publishing, 2016)
Summary- Jeune syndrome (Asphyxiating thoracic dysplasia) is a rare dystrophy of the skeleton, inherited as an autosomal recessive condition. Patients develop a narrowed thorax, rhizomelic dwarfism, and hepatic, renal, and pancreatic abnormalities. High rates of pulmonary hypoplasia and pulmonary hypertension have been reported. Some patients die in early stages of life due to respiratory failure. The case of a patient referred with a history of severe asphyxiating birth, who had been diagnosed with Jeune syndrome and later hypertrophic cardiomyopathy (HCM) upon echocardiographic examination is described in the present report. This rare disease is discussed with respect to the current literature, as the present is the first reported case to be accompanied by HCM.